2015
DOI: 10.1016/j.jtcvs.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Symptom recovery after thoracic surgery: Measuring patient-reported outcomes with the MD Anderson Symptom Inventory

Abstract: Objectives Measuring patient-reported outcomes (PROs) has become increasingly important for assessing quality of care and guiding patient management. However, PROs have yet to be integrated with traditional clinical outcomes (such as length of hospital stay) to evaluate perioperative care. This study aimed to utilize longitudinal PRO assessments to define the postoperative symptom-recovery trajectory in patients undergoing thoracic surgery for lung cancer. Methods Newly diagnosed patients (N=60) with stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 31 publications
3
77
2
Order By: Relevance
“…We have shown that postdischarge symptom burden was easily captured by an IVR system presenting MDASI symptom-severity items to patients at home (2). We have also demonstrated the MDASI’s sensitivity to important differences in symptom severity by the type of procedures presented here (open thoracotomy vs VATS) (19). …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We have shown that postdischarge symptom burden was easily captured by an IVR system presenting MDASI symptom-severity items to patients at home (2). We have also demonstrated the MDASI’s sensitivity to important differences in symptom severity by the type of procedures presented here (open thoracotomy vs VATS) (19). …”
Section: Discussionmentioning
confidence: 73%
“…We have previously reported on the utility of symptom-severity measurement from repeated administration of the MD Anderson Symptom Inventory (MDASI) after thoracic surgery (19). Here, we hypothesized that MDASI interference, as a measure of daily functioning, would be sensitive to differences in the recovery trajectory related to surgery type (open thoracotomy vs. VATS).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced recovery after surgery pathways have increasingly been applied to treat many patients who have undergone thoracic surgery, and symptomatic recovery after thoracic surgery has become increasingly important to assess quality of care and guide patient management . A cough, one of the most common respiratory symptoms after surgery, is an important determinant of quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal PRO assessments were used to define the postoperative symptom recovery trajectory in patients undergoing thoracic surgery for lung cancer [35]. By using the MD Anderson Symptom Inventory [35], the most-severe postoperative symptoms were fatigue, pain, shortness of breath, disturbed sleep, and drowsiness. The median time to return to mild symptom severity for these 5 symptoms was shorter than the time to return to the baseline severity with fatigue taking longer.…”
Section: Discussionmentioning
confidence: 99%
“…The median time to return to mild symptom severity for these 5 symptoms was shorter than the time to return to the baseline severity with fatigue taking longer. It is an effective strategy for evaluating the perioperative care in order to assess symptoms from the patient's perspective throughout the postoperative recovery period [35]. It is a sensitive tool for detecting symptomatic recovery to use the symptom inventory with an expected relationship among the surgical procedure type, preoperative performance status, and comorbid conditions [35].…”
Section: Discussionmentioning
confidence: 99%